Analisis Tingkat Pemahaman Pengguna Facebook Dalam Melindungi Data Privasi Berdasarkan Gender Di Kota Surabaya - Rohman, Muhammad Kholilur; Izzuddin, Muhammad Andik; Kunaefi, Anang (STIKOM Tunas Bangsa Pematangsiantar, 2025)
Social media users in Indonesia have reached 191.4 million, with Facebook accounting for 81.3% of the total. However, only 50% of users understand the security aspects that Facebook offers, despite the platform reporting 600,000 hacking attempts every day. This study aims to determine the level of understanding of Facebook users in Surabaya City in maintaining data privacy, as well as analyzing differences in user behavior based on gender. The questions in this study were designed based on the Data Detox Kit (DDK). The findings show that the factors “Control Your Smartphone Data” and “Escape The Defaults” influence data privacy concerns. Meanwhile, Surabaya people already tend to utilize Facebook's security features wisely. In the aspect of “Shift Your Settings,” Surabaya respondents showed disagreement that password negligence was the cause of data theft. Results also show that the difference in behavior between male and female users is not significant.